Strengthening China's Technological Capability - Yusuf, Shahid (World Bank, Washington, DC, 2012)
China is increasing its outlay on research and development and seeking to build an innovation system that will deliver quick results not just in absorbing technology but also in pushing the technological envelope. China's spending on R&D rose from 1.1 percent of GDP in 2000 to 1.3 percent of GDP in 2005. On a purchasing power parity basis, China's research outlay was among the world's highest, far greater than that of Brazil, India, or Mexico. Chinese firms are active in the fields of biotechnology, pharmaceuticals, alternative energy sources, and nanotechnology. This surge in spending has been parallel by a sharp increase in patent applications in China, with the bulk of the patents registered in the areas of electronics, information technology, and telecoms. However, of the almost 50,000 patents granted in China, nearly two-thirds were to nonresidents. This paper considers two questions that are especially important for China. First, how might China go about accelerating technology development? Second, what measures could most cost-effectively deliver the desired outcomes? It concludes that although the level of financing for R&D is certainly important, technological advance is closely keyed to absorptive capacity which is a function of the volume and quality of talent and the depth as well as the heterogeneity of research experience. It is also a function of how companies maximize the commercial benefits of research and development, and the coordination of research with production and marketing.